Analysis of Inclusive Economic Growth in West Sumatra - Dicky Rustam; Nasri Bachtiar (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2024)
This study aims to analyze the effect of inclusive economic growth in the regencies and cities of West Sumatra. The research utilizes panel data comprising a 5-year time series and a cross-section of 19 regencies and cities, resulting in a total of 95 observations. The dependent variable in this study is inclusive economic growth, while the independent variables include education, health, and government spending. The analytical method employed is panel data regression analysis. Based on the Chow test, Hausman test, and Lagrange Multiplier test, the best model selected is the Random Effect Model (REM). The classical assumption tests indicate that the data satisfy the requirements for normality and multicollinearity. The results of the panel data regression analysis reveal that education and health have a significant negative effect on inclusive economic growth, whereas government spending has a significant positive effect. These findings suggest that the government should focus on improving the quality of education and healthcare services and optimizing government spending to achieve inclusive economic growth. Such efforts should also aim to reduce poverty and income inequality.